Sensitive and multicolor detection of nitrite based on iodide-mediated etching of gold nanostars. Issue 93 (3rd November 2022) - Hong, Chengyi; Li, Dandan; Cao, Siying; Huang, Xin; Yang, Hongfen; Yang, Dan; Huang, Zhiyong; Cai, Ren; Tan, Weihong
Abstract : A colorimetric method was reported for the determination of nitrite with high selectivity and sensitivity based on iodide-mediated etching of gold nanostars. Abstract : Excessive intake of nitrite is a serious risk to human health. Research on the method of detecting nitrite in food is of great significance to avoid this issue. In this work, we report a colorimetric method based on iodide-mediated etching of gold nanostars (Au NSs) for the determination of nitrite with high selectivity and sensitivity. In the presence of iodide, the strong affinity between iodide and Au NSs results in the rapid etching of Au NSs into spherical gold nanoparticles, resulting in significant changes in the surface plasmon resonance (SPR) spectrum and the solution color. Because nitrite can oxidize iodide under acidic conditions, the etching degree of Au NSs could be controlled by adding different nitrite concentrations to consume iodide, leading to quantitative detection of nitrite. Under the optimal conditions, nitrite exhibits a good linear relationship with the absorption ratio ( A 820 nm / A 570 nm ) in the concentration range of 2–300 μM, with a detection limit of 0.4 μM. The as-proposed method was successfully applied to determination of nitrite in cabbage and sausage, and the results showed good reproducibility and accuracy.